7 inch Digital Micro Shutter Display Driven by IGZO Oxide TFT. Issue 1 (June 2014) - Kubota, Akinori; Nakano, Taketoshi; Nishiki, Hirohiko; Hara, Takeshi; Kitakado, Hidehito; Yamashita, Toshihiro; Ban, Atsushi; Imaya, Akihiko; Taniguchi, Yoji; Tanaka, Yoshinori
Abstract Digital Micro Shutter (DMS) Display based on MEMS design and process technologies provides wide color gamut, wide operating temperature range and low power consumption, compared with LCD and OLED which widely are used at the present time. Conventionally, DMS display was driven by LTPS TFT because of its high frequency operation. Oxide TFT as represented by IGZO has higher performance and reliability than a‐Si TFT, as well as better productivity for large display than LTPS TFT. The IGZO oxide TFT can be applied to drive DMS display with good performance. It means that uniquely high performance and large size DMS displays can be produced without significant investment. In this paper, technologies and performance of 7 inch diagonal DMS display are explored.